An Intensive Analysis of the Energy Management System for Hybrid Electric Vehicles and Electric Drive System Powered by Renewable Energy Sources - Zaman, Md Rakibur; Hoque, Md Reazul; Ali, Md Sumon (Peneliti Teknologi Teknik Indonesia, 2024)
The Energy Management System (EMS) used in Hybrid Electric Vehicles (HEVs) with an electric drive system powered by renewable energy sources is thoroughly investigated in this study. The study focuses on the crucial elements of encouraging sustainability and maximizing energy efficiency in transportation. The analysis focuses on the EMS's integration with renewable energy sources like solar, wind, biomass and mechanical vibration. This research is thoroughly reviewed by explaining the efficient management of the power flow between the internal combustion engine, electric motor, and renewable energy inputs, advanced control algorithms and optimization strategies. By incorporating solar panels into the design of a vehicle, the demand on the primary power source is decreased and electricity can be produced to fuel auxiliary systems like air conditioning. It is possible to use wind energy to create electricity for the car's auxiliary systems and electronics. Under various driving conditions and operational scenarios, the study assesses how well the suggested EMS performs, taking into account variables like fuel economy, emissions reduction, and overall system reliability. Testing in real-world scenarios confirms the system's efficacy and offers perceptions into its usefulness. The study explores the effects of fluctuating renewable energy availability and suggests adaptable tactics to strengthen the system's resistance to shifting circumstances. The research will pave the way for the creation of reliable EMS solutions for HEVs and provide environmentally friendly and sustainable mobility. In order to promote a more environmentally friendly and economically viable paradigm for hybrid electric vehicles, the study intends to direct future developments in the integration of renewable energy sources into electric drive systems. Enhanced predictive capabilities can make well-informed decisions about power distribution and consumption by assessing real-time data, weather forecasts, traffic patterns, and driver behavior. This can enhance energy management. The goal of the review is to develop and enhance renewable energy-based energy harvesting technology. These technologies' increased weight reduction and increased efficiency will make it easier to integrate them into electric drive systems.